1998
DOI: 10.1128/jb.180.4.938-944.1998
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of Outer Membrane Protein TolC, a Possible Member of the mar-sox Regulon, in Maintenance and Improvement of Organic Solvent Tolerance of Escherichia coli K-12

Abstract: Escherichia coli mutants with improved organic solvent tolerance levels showed high levels of outer membrane protein TolC and inner membrane protein AcrA. The TolC level was regulated positively by MarA, Rob, or SoxS. A possible mar-rob-sox box sequence was found upstream of the tolC gene. These findings suggest that tolC is a member of the mar-sox regulon responsive to stress conditions. When a defective tolC gene was transferred to n-hexane- or cyclohexane-tolerant strains by P1 transduction, the organic sol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
49
0

Year Published

2000
2000
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 173 publications
(50 citation statements)
references
References 49 publications
1
49
0
Order By: Relevance
“…The Escherichia coli soxRS regulon is composed of at least 17 related genes which respond to the redox status of the cell (Greenberg et al, 1990;Liochev et al, 1994;Ma et al, 1996;Aono et al, 1998). SoxR is a dimeric sensor with two [2Fe-2S] centers that detects oxidative stress and induces expression of soxS gene, which encodes a positive transcriptional regulator belonging to the AraC/XylS family that, in turn, induces expression of the genes of the sox regulon (Amábile-Cuevas & Demple, 1991;Wu & Weiss, 1992;Li & Demple, 1994;Ding et al, 1996;Pomposiello et al, 2001).…”
Section: Regulation Of Nitroreductase Gene Expressionmentioning
confidence: 99%
“…The Escherichia coli soxRS regulon is composed of at least 17 related genes which respond to the redox status of the cell (Greenberg et al, 1990;Liochev et al, 1994;Ma et al, 1996;Aono et al, 1998). SoxR is a dimeric sensor with two [2Fe-2S] centers that detects oxidative stress and induces expression of soxS gene, which encodes a positive transcriptional regulator belonging to the AraC/XylS family that, in turn, induces expression of the genes of the sox regulon (Amábile-Cuevas & Demple, 1991;Wu & Weiss, 1992;Li & Demple, 1994;Ding et al, 1996;Pomposiello et al, 2001).…”
Section: Regulation Of Nitroreductase Gene Expressionmentioning
confidence: 99%
“…Piddock et al [70] found no di¡erences in the DNA sequence of acrR and the promoter region of acrAB between the MAR isolates and the pre-therapy parent strain, suggesting that any mutation mediating resistance is more likely to be found in another regulatory gene. It would be interesting to examine whether the expression of a Rob homologue is increased in these isolates, as it is known that this protein a¡ects the function of the AcrAB e¥ux pump in E. coli [71,72]. Accumulation of cipro£oxacin, tetracycline and chloramphenicol by some of the MAR isolates of S. Typhimurium was increased by CCCP but remained well below the concentrations accumulated by the pre-therapy isolate [70].…”
Section: Multiple Drug Resistance and E¥ux In Human Isolatesmentioning
confidence: 99%
“…The outer membrane protein TolC belongs to a family of envelope proteins found in all Gram-negative bacteria and is essential for the expulsion of a plethora of compounds (Eswaran et al ., 2003). TolC is not only important for the efflux of small compounds such as organic solvents and antibiotics, but also for the export of large proteins such as α -haemolysin (Aono et al ., 1998;Vakharia et al ., 2001;Nishino et al ., 2003).…”
Section: Introductionmentioning
confidence: 99%